The Efficacy of Oncolytic Viruses in Reducing Neoplasms: A Scoping Review - Maroja, Maria Eduarda Duarte; Almeida, Maria Eduarda Gomes de; Lavalle, Manuela Souto Garcia; Tompson, Antônio Carlos de Melo; Schwartz, Amanda Cirne; Muniz, Kalyel Gomes; Baz, Mateus Henrique Dornelles; Soares da Silva, Paulo Gabriel; Silva, Hugo Rafael de Souza e (Brazilian Journal of Implantology and Health Sciences, 2024)
Pancreatic cancer is one of the cancers with the highest mortality rate, largely due to the aggressiveness of the tumor cells and the lack of obvious symptoms at the beginning of the disease. Based on this, the present review aims to analyze the effectiveness of using oncolytic viruses in the treatment of pancreatic neoplasms. To this end, using the PCC research strategy, an acronym for eligibility criteria that means Population, Concept, and Context, the scientific databases PubMed/MEDLINE, LILACS, EMBASE, and ScienceDirect were used. After applying the processes of inclusion, exclusion, selection, data extraction, and assessment of the Level of Evidence, the results were six articles analyzed and used for the scoping review. At the end of the analysis of these articles, two of them detected the DNA of the viruses in the patients’ blood, two presented grade I-II adverse events, and two used the same virus. Thus, five of the six articles analyzed demonstrated positive results, with the sixth being considered inconclusive. Therefore, it can be concluded that the treatment of pancreatic neoplasms with the use of oncolytic viruses, depending on the virus and the doses used, presents positive prospects for regression or interruption of the worsening of the disease, proving to be a source of hope for the future.